(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article written about origin of folk literature. Besides that, folk music vividly depicts people’s lives, their attitudes toward reality, and various inner experiences through a variety of sound colors. Song enhances people’s spiritual and moral world by influencing their emotions.This article highlights the important role of folk song in the moral and aesthetic education of students